Investigating the Influence of Attitude, Knowledge, Promotional Exposure, and Self-Efficacy on Compliance Behavior of Income Zakat - HAJI-OTHMAN, YUSUF; YUSUFF, MOHD SHOLEH SHEH; FISOL, WAN NAZJMI MOHAMED (The journal of contemporary issues in business and government, 2021)
As of April 2016, out of 68,000 Muslim federal servants in Kedah, a total of 40,453 paid zakat to Kedah State Zakat Board (KSZB) through a monthly deduction scheme. It means 59.49 percent of potential Muslim federal servants working in the state of Kedah paid zakat through a monthly deduction scheme in Kedah. However, Muslim public educators, who are part of Muslim public servants, have higher income zakat compliance behavior than the rest of Muslim public servants in Kedah. Despite a religious decree on the compulsory position of zakat on employment income in Malaysia, many Muslims still fail to fulfill their religious obligation to pay. Studies on zakat compliance have shown mixed and inconclusive evidence regarding the determinants of income zakat compliance. Hence, this study investigates the influence of attitude, knowledge, promotional exposure, and self-efficacy on compliance behavior of income zakat in Kedah, Malaysia. This study employs the quantitative approach using PLS-SEM to analyze primary data collected using a questionnaire instrument to determine significant determinants of compliance behavior of income zakat. This study reveals that attitude and self- efficacy have significant relationships with the compliance behavior of income zakat. However, this study discovers that knowledge and promotional exposure are not significant determinants of compliance behavior of income zakat in Kedah. This study is hoped to provide evidence that could be used as guidance for suitable policy and measures by Kedah State Zakat Board to improve zakat collection in the future.